2004
DOI: 10.1002/gene.20045
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear β‐catenin‐dependent Wnt8 signaling in vegetal cells of the early sea urchin embryo regulates gastrulation and differentiation of endoderm and mesodermal cell lineages

Abstract: The entry of beta-catenin into vegetal cell nuclei beginning at the 16-cell stage is one of the earliest known molecular asymmetries seen along the animal-vegetal axis in the sea urchin embryo. Nuclear beta-catenin activates a vegetal signaling cascade that mediates micromere specification and specification of the endomesoderm in the remaining cells of the vegetal half of the embryo. Only a few potential target genes of nuclear beta-catenin have been functionally analyzed in the sea urchin embryo. Here, we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(118 citation statements)
references
References 38 publications
(25 reference statements)
6
111
0
1
Order By: Relevance
“…This experiment, which has been repeated with molecular markers (14), means that micromeres execute signaling functions that have inductive effects on adjacent cells. We now know that between fourth and ninth cleavage (5-12 h after fertilization) the micromeres in fact express three different intercellular signaling ligands: (i) Wnt8, which enhances nuclearization of ␤-catenin in recipient cells, including themselves (15)(16)(17); (ii) a still undefined ''early signal (ES),'' which is received by adjacent cells in the fourth-to sixth-cleavage interval and is required by them for the normal process of endomesoderm specification (18); and (iii) from seventh cleavage, the Notch ligand Delta. Reception of this signal causes the ring of cells then immediately adjacent to the micromere lineage to assume mesodermal fate (19,20).…”
Section: Resultsmentioning
confidence: 99%
“…This experiment, which has been repeated with molecular markers (14), means that micromeres execute signaling functions that have inductive effects on adjacent cells. We now know that between fourth and ninth cleavage (5-12 h after fertilization) the micromeres in fact express three different intercellular signaling ligands: (i) Wnt8, which enhances nuclearization of ␤-catenin in recipient cells, including themselves (15)(16)(17); (ii) a still undefined ''early signal (ES),'' which is received by adjacent cells in the fourth-to sixth-cleavage interval and is required by them for the normal process of endomesoderm specification (18); and (iii) from seventh cleavage, the Notch ligand Delta. Reception of this signal causes the ring of cells then immediately adjacent to the micromere lineage to assume mesodermal fate (19,20).…”
Section: Resultsmentioning
confidence: 99%
“…The five cis-regulatory modules derive from three genes that encode transcription factors [namely, gatae (22), brachyury, and otx (23)] and two genes that encode signaling ligands [namely, delta (24) and wnt8 (25)]. The endo16 gene, also included in the analysis, encodes a terminal differentiation protein of the endoderm (26).…”
Section: Methodsmentioning
confidence: 99%
“…Depending which pathway becomes activated Wnts are subdivided into two classes; canonical and non-canonical according to the ability to induce accumulation of β-catenin in the nucleus. Signaling through some Wnts such as; Wnt1 (Hinck et al, 1994;Young et al, 1998;Shimizu et al, 1997), Wnt3a (Shimizu et al, 1997) and Wnt8 (Wikramanayake et al, 2004;Kohn and Moon, 2005) has been shown to correlate with accumulation of β-catenin in the nucleus and transcriptional changes, while signaling trough others like Wnt5a (Shimizu et al, 1997;Kikuchi et al, 2012) and Wnt11 (Kohn and Moon, 2005;Tada and Smith, 2000;Pandur et al, 2002) is β-catenin-independent and involves regulation of cytoskeleton or calcium release. All the metazoan species express Wnt genes and all of those genes encode secreted proteins based on their amino acid structure and biochemical characterization (Coudreuse and Korswagen, 2007;Smolich et al, 1993).…”
Section: Wnt Signaling Pathwaysmentioning
confidence: 99%